2018
DOI: 10.1099/jmm.0.000796
|View full text |Cite
|
Sign up to set email alerts
|

Development of a species-specific PCR-RFLP targeting rpoD gene fragment for discrimination of Aeromonas species

Abstract: This method provides an alternative method for laboratory identification, surveillance and epidemiological investigations of clinical and environmental specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…For example, Hiney et al (1992) reported a polymerase chain reaction (PCR) that was capable of detecting ~ 2 cells of A. salmonicida, whereas Høie et al (1997) detected 10 3 and 10 4 colony forming units (CFUs) of A. salmonicida in 100 ml of kidney suspension with 16S rRNA sequencing and plasmid primers, respectively. Subsequent developments included nested PCR (Taylor and Winton 2002), terminal-restriction fragment length polymorphism (RFLP) (Nilsson and Strom 2002), PCR-RFLP (Puah et al 2018), multiplex PCR (Chapela et al 2018), real-time PCR (Keeling et al 2013), quantitative real-time-PCR (Du et al 2017), real-time recombinase polymerase amplification (Pang et al 2019) and reverse transcription-multiplex PCR (Rattanachaikunsopon and Phumkhachorn 2012). All these techniques reported extremely high levels of sensitivity, detecting numbers of cells well below the level associated with occurrences of clinical disease (Austin and Austin 2016).…”
Section: Culture-independent Methods-molecular Biologymentioning
confidence: 99%
“…For example, Hiney et al (1992) reported a polymerase chain reaction (PCR) that was capable of detecting ~ 2 cells of A. salmonicida, whereas Høie et al (1997) detected 10 3 and 10 4 colony forming units (CFUs) of A. salmonicida in 100 ml of kidney suspension with 16S rRNA sequencing and plasmid primers, respectively. Subsequent developments included nested PCR (Taylor and Winton 2002), terminal-restriction fragment length polymorphism (RFLP) (Nilsson and Strom 2002), PCR-RFLP (Puah et al 2018), multiplex PCR (Chapela et al 2018), real-time PCR (Keeling et al 2013), quantitative real-time-PCR (Du et al 2017), real-time recombinase polymerase amplification (Pang et al 2019) and reverse transcription-multiplex PCR (Rattanachaikunsopon and Phumkhachorn 2012). All these techniques reported extremely high levels of sensitivity, detecting numbers of cells well below the level associated with occurrences of clinical disease (Austin and Austin 2016).…”
Section: Culture-independent Methods-molecular Biologymentioning
confidence: 99%
“…Using the amplified rpoD gene sequence and digested with Alu I, the species of individual isolates was determined (Puah, Khor, et al, 2018). The digested products were analysed using Agilent automated electrophoresis system and Agilent 2,100 Bioanalyzer (Agilent Technologies) and patterns generated (Figure 2) were analysed by Agilent 2,100 Expert Software.…”
Section: Methodsmentioning
confidence: 99%
“…The digested products were analysed using Agilent automated electrophoresis system and Agilent 2,100 Bioanalyzer (Agilent Technologies) and patterns generated (Figure 2) were analysed by Agilent 2,100 Expert Software. Species of individual isolates was determined by comparing RFLP patterns with the fragment sizes of the reference strains of all Aeromonas species (Puah, Khor, et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations